Regulatory role of ceRNA network in B lymphocytes of patients with immune thrombocytopenia - Xin He; Nianbin Li; Donglan Liu; Mengtong Zang; Manjun Zhao; Ningyuan Ran; Chunyan Liu; Limin Xing; Huaquan Wang; Ting Wang; Zonghong Shao (Taylor & Francis Group, 2023)
AbstractObjective High-throughput sequencing was used to screen expressing differences of miRNA, lncRNA, and mRNA in CD19+ B peripheral blood samples of newly diagnosed immune thrombocytopenia (ITP) patients and healthy controls. The study aimed to explore the regulatory role of ceRNA network in the pathogenesis of dysfunctional CD19 + B lymphocytes of ITP patients.Methods CD19+ B lymphocytes were isolated from peripheral blood samples of ITP patients and their healthy counterparts. High-throughput sequencing was used to screen for the expression of miRNA, lncRNA, and mRNA of ITP patients and healthy controls, which were analysed by the ceRNA network. Moreover, qPCR was used to verify the differential expression of miRNA, lncRNA, and mRNA in ITP patients and healthy controls. The correlation between differentially expressed miRNA, lncRNA, mRNA, and B lymphocyte subsets was also analysed.Results The CD19+ B lymphocytes of 4 newly diagnosed ITP patients and 4 healthy controls were sequenced and analysed. There were 65 differentially expressed lncRNA and 149 mRNA forming a ceRNA network showed that 12 lncRNA and 136 differentially expressed mRNA were closely associated. Similarly, miR-144-3p, miR-374c-3p, and miR-451a were highly expressed in ITP patients, as confirmed by qPCR, which was consistent with the high-throughput sequence results. LOC102724852 and CCL20 were highly expressed in ITP patients, while LOC105378901, LOC112268311, ALAS2, and TBC1D3F were not as compared to healthy controls, which was consistent with the high-throughput sequence results. In addition, the expression of miR-374c-3p, LOC112268311, LOC105378901, and CXCL3 were correlated with the percentage of B lymphocyte subsets.Conclusions The ceRNA network of miRNA, lncRNA, and mRNA in peripheral CD19 + B lymphocytes plays an essential role in the pathogenesis of ITP.